Resiliensi Kebijakan Politik Pemerintah Turki Terhadap Wabah Internasional Coronavirus Disease 19 - Nanda Setia (Department of International Relations, University of Mataram, 2022)
The cases of COVID-19 is now a big problem in the international sphere after the WHO announced that this case had become an international outbreak. All countries in the world are affected. Turkey is one of the countries in West Asia that has been affected by COVID-19. At the beginning of 2022, Turkey was considered successful in recovering from this international outbreak, so that it won praise from the World Health Organization (WHO). This paper discusses how this outbreak began in Turkey and the form of handling carried out by the Turkish government, what policies do in controlling the spread of COVID-19. This writing uses historical research methods with the main source from the WHO Europe website and various secondary sources from international journals that support this writing.